The upward shift of hilar structures and tracheal deviation in pleuroparenchymal fibroelastosis - Ishii, Hiroshi; Kinoshita, Yoshiaki; Kushima, Hisako; Ogura, Takashi; Watanabe, Kentaro (Multidisciplinary Respiratory Medicine, 2019)
The upward shift of hilar structures is a characteristic finding on chest radiographs in pleuroparenchymal fibroelastosis (PPFE). However, the relationship between the hilar shift and clinical parameters is unclear. In this study, the ratio of the length of the lung apex to the hilum and the length of the apex to the base of the right lung was measured using chest computed tomography (CT) at the time of the diagnosis, and the relationship with clinical parameters was investigated. We also examined the deviations of the trachea on chest radiographs and compared them with those in idiopathic pulmonary fibrosis (IPF) and early-stage lung cancer. Thirty-eight PPFE patients in a previous study included 20 patients who simultaneously showed the lower lobe lesions. The median ratio of the length of the apex to the hilum/apex to the base was 0.32 (range: 0.10–0.41) in PPFE, and this value was significantly lower than that in IPF (0.39; 0.32–0.45, n = 38) and in lung cancer (0.41; 0.33 to 0.45, n = 38) (p < 0. 001, respectively). However, the ratio of the length of the apex to the hilum/apex to the base did not correlate with the dyspnea scale, body mass index or pulmonary function in PPFE. Tracheal deviations were observed in 41 out of 52 PPFE patients (36 with rightward deviations, 5 with leftward deviations) and in 30 out of 52 IPF patients (30 with rightward deviations) (p = 0.01). Although the existence of the upward shift of hilar structures on chest images might lead to a diagnosis of PPFE, the extent of hilar elevation does not necessarily reflect disease progression. Tracheal deviation is not a specific finding for PPFE.